2020
DOI: 10.3390/f11111153
|View full text |Cite
|
Sign up to set email alerts
|

Linking Tree Health, Rhizosphere Physicochemical Properties, and Microbiome in Acute Oak Decline

Abstract: Forest decline diseases are complex processes driven by biotic and abiotic factors. Although information about host–microbiome–environment interactions in agricultural systems is emerging rapidly, similar studies on tree health are still in their infancy. We used acute oak decline (AOD) as a model system to understand whether the rhizosphere physicochemical properties and microbiome are linked to tree health by studying these two factors in healthy and diseased trees located in three sites in different AOD sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 70 publications
(59 reference statements)
2
12
0
Order By: Relevance
“…Our analysis of the abundance of Acute Oak Decline-associated bacteria showed differences between the geographical sites. This is in line with a study of the oak rhizosphere, which found differences in the bacterial composition of the root microbiome between sites [13]. It is also in line with phyllosphere studies on other tree species, reviewed by Rastogi et al [61] in which geographical location has been shown to be a driver of bacterial community composition.…”
Section: Discussionsupporting
confidence: 88%
“…Our analysis of the abundance of Acute Oak Decline-associated bacteria showed differences between the geographical sites. This is in line with a study of the oak rhizosphere, which found differences in the bacterial composition of the root microbiome between sites [13]. It is also in line with phyllosphere studies on other tree species, reviewed by Rastogi et al [61] in which geographical location has been shown to be a driver of bacterial community composition.…”
Section: Discussionsupporting
confidence: 88%
“…Affected sites are more likely to be found in warmer areas of Britain and areas of low rainfall [11,12]. Soil pH, and the rhizosphere microbiome, have been found to differ between symptomatic and asymptomatic trees at some sites [13,14]. A study that included Hatchlands Park and Sheen Wood (both of which are studied here, see below) found that the bacterial composition of the rhizosphere differed between sites and tree health conditions [13].…”
Section: Introductionmentioning
confidence: 88%
“…Disease can then be considered as arising from a perturbation of a healthy microbiome. The plant microbiome has received much attention over the last decade (Mercado-Blanco et al 2018;Baldrian 2019;Vonaesch et al 2018), in both food crops (Ding et al 2019) and forest trees (Feau and Hamelin 2017;Koskella et al 2017;Pinho et al 2020). It has long been recognized that plant-associated microbiomes, the phytobiome (e.g., the phyllosphere, endophyte, and rhizosphere microbiome), will affect directly and/or indirectly disease development (Glaeser et al 2019;Martin et al 2019;Rabiey et al 2019;Tsolakidou et al 2019).…”
Section: Promises and Challenges For Holobiont And Microbiome Research: An Expanded Perspective On Microbial Interactions Biological Contmentioning
confidence: 99%